Pengaruh Bauran Promosi terhadap Pengambilan Keputusan Memilih Universitas Muhammadiyah Sidoarjo (UMSIDA) (Studi pada Mahasiswa Alumni SMA Kemala Bhayangkari 3 Porong) - Ervina Surya Setyowati; Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2017)
This study aims to determine the effect of promotional mix of decision making in choosing Universitas Muhammadiyah Sidoarjo (UMSIDA) on alumni of SMA Kemala Bhayangkari 3 Porong. This type of research is quantitative, with the type of descriptive correlational research. Population and sample in this research are alumni of SMA Kemala Bhayangkari 3 Porong counted 91 people. Data collection using Likert Scale, with five alternative answers or scores. Methods of data collection using questionnaires with multiple linear regression analysis techniques using SPSS V16.0 program. The result of this research is promotion mix influencing decision making process of choosing UMSIDA 45,9% and the rest equal to 54,1% influenced by factors not examined. From the partial test, the most influential promotional mix in decision making is advertising, while public relations and personal selling have no influence in decision making of UMSIDA.